Mine, Yours, Ours? Focusing on Affective Publicness in Urban Public Space - Talko,Anna (2025)
This thesis explores how public spaces are emotionally and socially experienced through introducing the concept of affective publicness, which is a framework for understanding the emotional and relational dynamics that shape urban public spaces. Departing from the theoretical frame of emotional geography and affective urbanism, the research investigates how affective publicness is felt and shaped in its users' daily interactions. Through the example of two public spaces in the Sorgenfri district of Malmö, this study asks: How is the publicness of public space perceived by the users of public space in Sorgenfri? And: What emotional, social, and spatial factors shape the affective atmospheres and perceptions of public space? Using a photo-elicitation method, the research proves that affective publicness is a multi-dimensional condition shaped by various forms of agency, encounters, experience and affective responses to design. Factors which shape the affective atmospheres of urban public space are identified as temporality, imagined futures, perception of community, safety, proximity and convenience, and non-commercial experiences. These findings contribute to ongoing debates about inclusivity and belonging in urban public space in entrepreneurial cities like Malmö. By highlighting the affective dimensions of public space, the study shows the importance of urban environments that are responsive to the everyday experiences of its users.
Keywords: publicness; urban public space; emotional geography; affective urbanism; affective publicness